2014
DOI: 10.1111/apt.12739
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal intraepithelial lymphocytosis is common in children without coeliac disease, and is not meaningfully influenced by Helicobacter pylori infection

Abstract: SUMMARY BackgroundIncreased numbers of duodenal intraepithelial lymphocytes (IELs) characterise coeliac disease (CD) but have also been described in noncoeliacs. Controversy exists regarding an association between increased IELs and infection with Helicobacter pylori, which is commonly found in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…It has been established that Hp infection causes duodenitis and induces intra‐epithelial lymphocytosis, whereby Hp infection may contribute to more severe damage in patients with CD. In this study, the histologic severity of duodenal lesions was not influenced by the presence of Hp infection, and it was comparable to the previous publications 12,21,30 . However, there are studies demonstrating milder inflammation in the duodenum of celiac patients when there was a concomitant Hp infection.…”
Section: Discussionsupporting
confidence: 90%
“…It has been established that Hp infection causes duodenitis and induces intra‐epithelial lymphocytosis, whereby Hp infection may contribute to more severe damage in patients with CD. In this study, the histologic severity of duodenal lesions was not influenced by the presence of Hp infection, and it was comparable to the previous publications 12,21,30 . However, there are studies demonstrating milder inflammation in the duodenum of celiac patients when there was a concomitant Hp infection.…”
Section: Discussionsupporting
confidence: 90%
“…For H. pylori -related duodenal lymphocytosis, eradication therapy should be proposed [139,140]. Antibiotics have shown effectiveness in both bacteria eradication and ME reversal [76]. Other intestinal infections require treatment that is targeted according to the etiologic agent, such as metronidazole for Giardia spp , rifaximin for SIBO, or fluoroquinolones for other bacterial species [141-143].…”
Section: Treatmentmentioning
confidence: 99%
“…In patients without CD, Hp had a marginal effect on the duodenal IEL counts, from an average of 15 IELs/100 to 17 (Hp negative vs. Hp positive respectively). The authors also showed a slight trend among the positive Hp patients to have more severe villous atrophy [21]. This finding contrasts those of both Villanacci and Aydogu, who reported higher rates of low-grade lesions among positive Hp celiac patients [22,23].…”
Section: Resultsmentioning
confidence: 60%
“…Several authors also a correlation with lymphocytic gastritis (LG) which is also the most frequent form of gastritis observed in celiac patients [8][9][10][11]20,21].…”
Section: Resultsmentioning
confidence: 98%